Investigation on the properties and structures of resveratrol-derived epoxy thermosets cured with an active ester. Issue 14 (24th March 2023) - Liu, Jiaming; Liu, Xiaohong; Cui, Xiaohua; Qin, Jingjing; Wu, Mengqin; Fu, Lifu; Shi, Min; Wang, Dingsong; Liang, Liyan
Abstract : In this work, two resveratrol-derived epoxy thermosets (REP/TAR and REP/TTR) were prepared, and their cross-linked structure and thermal degradation were analyzed. Abstract : Using biomass resources to prepare thermosets seems to have become a trend in the future of a sustainable society, and an active ester may be an excellent epoxy hardener for the electronic packaging field. In this work, we synthesized a resveratrol-derived epoxy (REP) and two resveratrol-derived active ester hardeners (triacetyl resveratrol (TAR), tri( m -toluoyl) resveratrol (TTR)), and then two resveratrol-derived bio-based epoxy thermosets (REP/TAR, REP/TTR) were prepared by the curing reaction of the epoxy and the hardener. The properties and structures of the thermosets were characterized and investigated. Results showed that the properties of REP/TAR in all aspects were better than those of REP/TTR; to be specific, the REP/TAR exhibited a higher gel fraction and better solvent resistance, indicating its better cross-linked network; the glass transition temperature of REP/TAR was higher and reached 177 °C (DMA) and the thermal stability of TEP/TAR was also better and the char yield at 600 °C was 46.5%. The main reason could be that the steric hindrance of acetyl groups in REP/TAR was smaller than that of m -toluoyl groups in REP/TTR. What's more, a novel analytical method was proposed for use in thermogravimetric analysis (TGA) to analyze the degradation process of thermosets, revealing a degradation process that was unique to the active ester cured epoxy thermosets. In all, the resveratrol-derived biobased epoxy thermosets could be a promising candidate for replacing fossil-derived thermosets and have potential application in the electronic packaging field, and the study on active ester hardeners might inspire the design and synthesis of subsequent active ester hardeners.